Ternary platinum alloy with transition metal for enhanced oxidative activity
By using ternary alloy nanoparticle catalysts, including platinum group metals and transition metal elements, and are supported on a refractory oxide support, the problem of inactivation of existing catalysts at high temperatures is solved, and high efficiency for CO, HC and NO Oxidation conversion and stability extend the service life of the catalyst.
Patent Information
- Application Number
- CN202380039280.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-10
- Filing Date
- 2023-06-09
- Publication Date
- 2025-01-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing catalysts are inactivated at high temperatures, especially the platinum-containing catalysts only have a decrease in activity after hydrothermal aging, resulting in a decrease in NO2 generated by NO oxidation, affecting SCR reaction activity, and the performance of diesel oxidation catalysts is degraded due to support sintering when exposed to high temperatures. .
Using a ternary alloy nanoparticle catalyst, it contains at least two transition metal elements alloyed platinum group metals, such as Pt, Pd, Ru, etc., and Ni, Co, Mn, Fe, etc., and is loaded on a refractory oxide support, through Specific synthesis methods and calcination steps ensure the stability and activity of the catalyst at high temperatures.
The efficiency of the catalyst to oxidative conversion of CO, HC and NO→NO2 is improved, and the stability is maintained after hydrothermal aging, reducing the deactivation of the catalyst and extending the service life.
Smart Images

Figure HDA0005124895290000011 
Figure HDA0005124895290000021 
Figure HDA0005124895290000031
Abstract
Description
[0001] This disclosure was made with government support under grant CHE-2102482 from the National Science Foundation. The government has certain rights in this disclosure.
[0002] The present invention relates to a method for treating an exhaust gas stream of an internal combustion engine to control hydrocarbons (HC), carbon monoxide (CO) and nitrogen oxides (NO x ) The oxidation catalyst, system and method for treating emissions of ammonia. The oxidation catalyst, treatment system and method include a ternary alloy nanoparticle catalyst; the ternary alloy nanoparticle catalyst includes a platinum group metal alloyed with at least two transition metal elements.
[0003] The exhaust gas stream of an internal combustion engine contains pollutants that pollute the air, such as hydrocarbons (HC), carbon monoxide (CO) and nitrogen oxides (NO x ). Typically, an oxidation catalyst comprising a noble metal such as a platinum group metal (PGM) dispersed on a refractory metal oxide support such as alumina is used to treat the exhaust gas of an internal combustion engine in order to convert HC and CO gaseous pollutants by catalyzing the oxidation of these pollutants into carbon dioxide and water. Typically, the oxidation catalyst is formed on a ceramic or metal substrate on which one or more catalyst coating compositions are deposited. In addition to converting gaseous HC and CO emissions, the oxidation catalyst containing the PGM also promotes the oxidation of NO to NO2, which enhances the downstream SCR reaction, especially at lower temperatures (≤250°C).
[0004] The catalyst is usually measured at its light-off temperature or the temperature at which 50% conversion is achieved (also known as T 50 ). Platinum-only catalysts can lose activity during use, especially after hydrothermal aging, leading to, for example, a reduction in NO2 generated from NO oxidation, which in turn leads to reduced downstream SCR activity, most notably at lower temperatures (≤250°C). From fresh to aged catalysts, NO2 / NO x Large variations in the ratio also lead to complications in calibrating the urea injection rate during catalyst deactivation caused by hydrothermal aging.
[0005] It is known that oxidation catalysts comprising precious metals dispersed on refractory metal oxide supports can be used to treat the exhaust of diesel engines to convert these pollutants by catalyzing the oxidation of hydrocarbon and carbon monoxide gaseous pollutants into carbon dioxide and water. Such catalysts are generally contained in a unit called a diesel oxidation catalyst (DOC) or more simply a catalytic converter, which is placed in the exhaust gas flow path of a diesel-powered engine to treat the exhaust gas before it is discharged into the atmosphere. Typically, the diesel oxidation catalyst is formed on a ceramic or metal substrate support (such as a flow-through monolithic support, as described below), and one or more catalyst coating compositions are deposited on the support. In addition to converting gaseous HC, CO and particulate matter, oxidation catalysts containing platinum group metals (which are generally dispersed on refractory oxide supports) also promote the oxidation of nitrogen monoxide (NO) to NO2.
[0006] An important factor in DOC design is catalyst deactivation after high temperature exposure. Thermally induced DOC deactivation may occur due to sintering of the catalytic components or the support. Sintering of the catalytic components involves the agglomeration or grain growth of initially well-dispersed catalytic sites. This agglomeration can lead to a loss of surface to volume ratio, thereby reducing catalytic performance. Alternatively, exposure of the DOC to high temperatures can lead to sintering of the catalytic support. This involves a loss of the support pore structure, which results in a loss of accessibility to the catalytically active sites.
[0007] S. Shiyao et al., “Surface oxygenation of multicomponent nanoparticles toward active and stable oxidation catalysts,” NATURE COMMUNICATIONS, Vol. 11, No. 1, December 1, 2020, deals with the synthesis of oxidation catalysts for the full oxidation of hydrocarbons (such as propane) by surface oxygenation of platinum alloy multicomponent nanoparticles.
[0008] L. Yang et al., "Role of Support-Nanoalloy Interactions in the Atomic-Scale Structural and Chemical Ordering for Tuning Catalytic Sites", JOURNAL OF THE AMERICAN CHEMICAL SOCIETY, Vol. 134, No. 36, September 12, 2012, discloses alloy nanoparticles as oxidation catalysts that can be supported on silica, titania or carbon, wherein the catalyst is used for the oxidation of CO.
[0009] Therefore, there remains a need for more effective catalysts for treating the exhaust of internal combustion engines. Specific needs include catalysts that can provide excellent CO, HC and NO→NO2 oxidation conversions and are stable to hydrothermal aging.
[0010] The present disclosure relates to an oxidation catalyst, which is a ternary alloy nanoparticle catalyst. The ternary alloy nanoparticle catalyst comprises a platinum group metal alloyed with at least two transition metal elements. The platinum group metal can be selected from Pt, Pd, Ru, Rh, Ir and Os; and the at least two transition metal elements can be selected from Ni, Co, Mn, Fe, V, Zn, Cu, Ti, Sc and Cr. The present disclosure also relates to a diesel oxidation catalyst comprising the above-mentioned ternary alloy nanoparticle catalyst.
[0011] The ternary alloy nanoparticle catalyst can be supported on a refractory oxide support, and the refractory oxide support can be selected from silica, delta-alumina, theta-alumina, gamma-alumina, Si-doped alumina, alkaline earth metal stabilized alumina, transition metal stabilized alumina, zirconia and titania.
[0012] The platinum group metal content of the ternary alloy nanoparticles may be less than or equal to about 80 atomic % of the metal content, and the weight ratio of the platinum group metal may be about 30 atomic % to about 50 atomic % of the metal content.
[0013] The at least two transition metal elements of the ternary alloy nanoparticles may have a combined ratio of about 20 atomic % to about 80 atomic % of the metal content.
[0014] The platinum group metal and at least two transition metal elements of the ternary alloy nanoparticle catalyst can be detected by TEM / EDS (transmission electron microscopy combined with energy dispersive X-ray spectroscopy), X-ray diffraction or a combination thereof.
[0015] After incorporation of different levels of at least two transition metals, the XRD of the ternary alloy nanoparticles may exhibit a 2θ value of Pt fcc (111) ranging from about 39.7° to about 42°.
[0016] The ternary alloy nanoparticle catalyst can be selected from PtNiCo and PtMnFe. The atomic ratio of the PtNiCo ternary alloy nanoparticle catalyst can be about 20%-80% Pt, about 1%-50% Ni and about 5%-40% Co. The atomic ratio of the PtMnFe ternary alloy nanoparticle catalyst can be about 15%-40% Pt, about 10%-50% Mn and about 10%-50% Fe.
[0017] The present disclosure also provides a method for preparing a ternary alloy nanoparticle catalyst, the ternary alloy nanoparticle catalyst comprising a platinum group metal alloyed with at least two transition metal elements. The method may include combining a precursor of the platinum group metal and a precursor of at least two transition metal elements with a capping agent in an organic solvent to form a solution; introducing a reducing agent into the solution to produce a colloidal suspension of the ternary alloy nanoparticle catalyst; collecting the ternary alloy nanoparticle catalyst and adsorbing it onto a refractory oxide support; and drying and calcining the adsorbed ternary alloy nanoparticle catalyst and the refractory oxide support.
[0018] The precursor of the platinum group metal can be selected from platinum (II) acetylacetonate, chloroplatinic acid, platinum (II) hydroxysulfite, tetraammine platinum (II) chloride and tetraammine platinum (II) nitrate. The precursor of the at least two transition metal elements can be selected from nickel (II) acetylacetonate and cobalt (III) acetylacetonate. The capping agent can be selected from citric acid, polyvinyl pyrrolidone, oleylamine, oleic acid and polyethylene glycol. The reducing agent can be selected from sodium borohydride, hydrazine, formic acid, sodium formate and amine-borane complex; 1,2-hexadecanediol and oleylamine. The refractory oxide support can be selected from silica, δ-alumina, θ-alumina, γ-alumina, Si-doped alumina, alkaline earth metal stabilized alumina, transition metal stabilized alumina, zirconium oxide and titanium dioxide.
[0019] The calcining step of the method may include calcining the ternary alloy nanoparticle catalyst and the refractory oxide support at about 800° C. for about 2 hours in a hydrogen atmosphere, followed by heating at about 260° C. for about 1 hour in air, and heating at about 590° C. for about 1 hour in air.
[0020] The nanoparticles of the ternary alloy catalyst may have an average particle size ranging from about 2 nm to about 10 nm.
[0021] The total platinum group metal content of the ternary alloy nanoparticle catalyst may be from about 0.1 wt % to about 5 wt % of the metal content.
[0022] Nanoparticles of ternary alloy catalysts usually retain the original atomic ratio of each element. Although the transition metal elements are present throughout the nanoparticles, enrichment usually occurs on the particle surface, which may be due to the oxophilic nature of the transition metals when calcined in air.
[0023] After hydrothermal aging, the nanoparticles of the ternary alloy catalyst become more Pt-rich (>90 atom%) and the transition metal elements become <10 atom%. All three elements are uniformly present throughout the particles.
[0024] The present disclosure also provides an exhaust gas treatment system comprising a ternary alloy nanoparticle catalyst as described herein, preferably comprising an oxidation catalyst composite according to any specific and preferred embodiment described herein. The ternary alloy nanoparticle catalyst can be positioned downstream of an internal combustion engine and in fluid communication with the internal combustion engine.
[0025] The present disclosure also provides a method for treating an exhaust gas stream containing HC and / or CO and / or NO→NO2 oxidation. The method may include passing the exhaust gas stream through a ternary alloy nanoparticle catalyst or oxidation catalyst composite or exhaust gas treatment system as described herein. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to provide an understanding of the embodiments of the present disclosure, reference is made to the accompanying drawings, which are exemplary and should not be construed as limiting the present disclosure.
[0027] Figure 1 (A) Example 1 (Pt 41 Ni 36 Co 23 )、(B) Comparative Example 3 (Pt 51 Ni 49 )、(C) Comparative Example 4 (Pt 63 Co 37 ) and (D) Example 3 (Pt dispersed on γ-Al2O3 41 Ni 36 Co 23 , ~0.72 wt% Pt).
[0028] Figure 2 TEM images of Example 2 at various Pt / Mn / Fe atomic ratios are shown: (A) Pt 13 Mn 27 Fe 60 , (B)Pt 38 Mn 29 Fe 33 , (C)Pt 86 Mn1Fe 13 , and Example 4 (D) Pt 38 Mn 29 Fe 33 TEM image of / Al2O3 at ~0.53 wt% Pt.
[0029] Figure 3 X-ray diffraction patterns of Example 1 (isolated PtNiCo), Comparative Example 1 (10 wt % Pt / Al 2 O 3 ), and Example 3 (PtNiCo / Al 2 O 3 , 10 wt % Pt) are shown.
[0030] Figure 4It is the elemental line distribution of the nanoparticles in Example 3 after 650°C / 50h HT aging (PtNiCo / Al2O3, ~0.72% Pt).
[0031] Figure 5 A comparison of the NO→NO2 activity of Example 3 and Comparative Example 1 before and after 650°C / 50h aging is shown, and the test was performed according to Example 5.
[0032] Figure 6 Example 3 (Pt 55 Ni 27 Co 18 / Al2O3) and NO2 / NO in Comparative Examples 1 and 2 x Ratio change (ΔNO2 / NO x , difference between fresh and aged), where all samples contained 1.85% Pt, were aged at 650°C / 50h, and tested according to Example 5.
[0033] Figure 7 Example 3 (Pt 55 Ni 27 Co 18 / Al2O3) and CO and HC light-off T of Comparative Examples 1 and 2 50 , where all samples contained 1.85% Pt, were aged at 650°C / 50h, and tested according to Example 5.
[0034] Figure 8 The Pt / Ni / Co atomic ratios from fresh to aged (650℃ / 50h) are shown. x Effect of ratio stability, tested according to Example 5 after hydrothermal aging at 650°C / 50h.
[0035] Fig. 9 The Pt / Ni / Co atomic ratios from fresh to aged (675℃ / 25h) are shown. x Influence of ratio stability, tested according to Example 6 after aging at 675°C / 25h.
[0036] Fig.10 Comparative Example 6 (Pt 44 Ni 56 / Al2O3, ~1.1 wt% Pt) and Comparative Example 7 (Pt 40 Co 60 / Al2O3, ~0.59 wt% Pt) and Comparative Example 1 (~1 wt% Pt) before and after aging (675°C / 25h) and tested according to Example 6.
[0037] Fig.11 Example 4 (Pt 37 Mn 50 Fe 13 / Al2O3, ~0.64 wt% Pt) and Comparative Example 2 (0.7 wt% Pt) before and after aging (650°C / 50h) and tested according to Example 5.
[0038] Fig.12 Comparative Example 5 (Pt 46 Mn 54 / Al2O3, ~1 wt% Pt) and Comparative Example 1, both of which are fresh samples and tested according to Example 6.
[0039] Fig.13 Comparative Examples 1 and 2 and Example 3 (Pt 55 Ni 27 Co 18 Comparison of CO-DRIFTS (diffuse reflectance infrared Fourier transform spectroscopy) intensity before and after hydrothermal aging (650°C / 50h) (atomic ratio). All samples contain 1.85 wt% Pt. CO adsorption experiments were performed after pretreatment at 400°C for 1 h in Ar, and the inset shows the expanded signal of the aged sample.
[0040] The present disclosure will now be described more fully. However, the present disclosure may be embodied in many different forms and should all be construed as limited to the embodiments described herein.
[0041] As used herein, unless otherwise specified, "a" or "an" entity refers to one or more of that entity, e.g., "catalyst" refers to one or more catalysts or at least one catalyst. Thus, the terms "a" (or "an"), "one or more" and "at least one" are used interchangeably herein.
[0042] As used herein, the term "about" means approximately, in the range of, roughly, or around. When the term "about" is used in conjunction with a numerical range, it modifies that range by extending the boundaries above and below the numerical values listed. Generally, the term "about" is used herein to modify a numerical value above and below the stated value by a variance of 10%.
[0043] As used herein, the term "alloy" refers to a material composed of two or more metallic elements joined by atomic bonding. The alloys of the present disclosure exhibit properties that differ from the individual properties of the elements that make up the alloy. The distribution of each element in the alloy can be affected by external treatments, resulting in enrichment of certain elements, typically on the particle surface.
[0044] As used herein, the term "stream" broadly refers to any combination of flowing gases that may contain solid or liquid particulate matter. The term "gas stream" or "exhaust stream" or "exhaust stream" refers to a stream of gaseous components, such as the exhaust gas of an internal combustion engine, which may contain entrained non-gaseous components such as liquid droplets, solid particles, etc. The exhaust stream of an internal combustion engine generally also contains combustion products (CO2 and H2O), incomplete combustion products (carbon monoxide (CO) and hydrocarbons (HC)), nitrogen oxides (NO x ), combustible and / or carbonaceous particulate matter (soot) and unreacted oxygen and nitrogen.
[0045] As used herein, "impregnated" or "impregnation" refers to the penetration of the catalytic material into the porous structure of the support material.
[0046] The catalysts of the present invention are suitable for treating exhaust gas streams of internal combustion engines such as gasoline, light diesel and heavy diesel engines. In some embodiments, such catalysts can be combined with other components, such as other catalyst compositions, to provide compositions and articles suitable for use as diesel oxidation catalysts or catalytic soot filters. The catalysts are also suitable for treating emissions from stationary industrial processes, removing harmful or toxic substances from indoor air, or for catalysis in chemical reaction processes.
[0047] The present disclosure relates to a ternary alloy nanoparticle catalyst comprising a platinum group metal alloyed with at least two transition metal elements. In some embodiments, the ternary alloy nanoparticle catalyst comprises two transition metal elements. In some embodiments, the ternary alloy nanoparticle catalyst comprises three transition metal elements. In some embodiments, the ternary alloy nanoparticle catalyst comprises four transition metal elements.
[0048] As used herein, the term "platinum group metal" (PGM) refers to a platinum group metal or an oxide thereof, such as platinum (Pt), palladium (Pd), ruthenium (Ru), rhodium (Rh), osmium (Os), iridium (Ir), oxides of any of the foregoing, and mixtures of any of the foregoing. In some embodiments, the PGM may be in any valence state.
[0049] In some embodiments, the platinum group metal of the ternary alloy nanoparticle catalyst is selected from Pt, Pd, Ru, Rh, Ir and Os. In some embodiments, the platinum group metal of the ternary alloy nanoparticle catalyst is Pt. In some embodiments, the platinum group metal of the ternary alloy nanoparticle catalyst is Pd. In some embodiments, the platinum group metal of the ternary alloy nanoparticle catalyst is a combination of Pt and Pd. In some embodiments, the platinum group metal of the ternary alloy nanoparticle catalyst is Ru. In some embodiments, the platinum group metal of the ternary alloy nanoparticle catalyst is Rh. In some embodiments, the platinum group metal of the ternary alloy nanoparticle catalyst is selected from Ir. In some embodiments, the platinum group metal of the ternary alloy nanoparticle catalyst is Os.
[0050] In some embodiments, the at least two transition metals of the ternary alloy nanoparticle catalyst are selected from nickel (Ni), cobalt (Co), manganese (Mn), iron (Fe), vanadium (V), zinc (Zn), copper (Cu), titanium (Ti), scandium (Sc) and chromium (Cr). In some embodiments, the at least two transition metals are Ni and Mn. In some embodiments, the at least two transition metals are Ni and Mn. In some embodiments, the at least two transition metals are Ni and Fe. In some embodiments, the at least two transition metals are Ni and V. In some embodiments, the at least two transition metals are Ni and Zn. In some embodiments, the at least two transition metals are Ni and Cu. In some embodiments, the at least two transition metals are Ni and Ti. In some embodiments, the at least two transition metals are Ni and Sc. In some embodiments, the at least two transition metals are Ni and Cr. In some embodiments, the at least two transition metals are Co and Mn. In some embodiments, the at least two transition metals are Co and Fe. In some embodiments, the at least two transition metals are Co and V. In some embodiments, the at least two transition metals are Co and Zn. In some embodiments, the at least two transition metals are Co and Cu. In some embodiments, the at least two transition metals are Co and Ti. In some embodiments, the at least two transition metals are Co and Sc. In some embodiments, the at least two transition metals are Co and Cr. In some embodiments, the at least two transition metals are Mn and Fe. In some embodiments, the at least two transition metals are Mn and V. In some embodiments, the at least two transition metals are Mn and Zn. In some embodiments, the at least two transition metals are Mn and Cu. In some embodiments, the at least two transition metals are Mn and Ti. In some embodiments, the at least two transition metals are Mn and Sc. In some embodiments, the at least two transition metals are Mn and Cr. In some embodiments, the at least two transition metals are Fe and V. In some embodiments, the at least two transition metals are Fe and Zn. In some embodiments, the at least two transition metals are Fe and Cu. In some embodiments, the at least two transition metals are Fe and Ti. In some embodiments, the at least two transition metals are Fe and Sc. In some embodiments, the at least two transition metals are Fe and Cr. In some embodiments, the at least two transition metals are V and Zn. In some embodiments, the at least two transition metals are V and Cu. In some embodiments, the at least two transition metals are V and Ti. In some embodiments, the at least two transition metals are V and Sc. In some embodiments, the at least two transition metals are V and Cr. In some embodiments, the at least two transition metals are Zn and Cu.In some embodiments, the at least two transition metals are Zn and Ti. In some embodiments, the at least two transition metals are Zn and Sc. In some embodiments, the at least two transition metals are Zn and Cr. In some embodiments, the at least two transition metals are Cu and Ti. In some embodiments, the at least two transition metals are Cu and Sc. In some embodiments, the at least two transition metals are Cu and Cr. In some embodiments, the at least two transition metals are Ti and Sc. In some embodiments, the at least two transition metals are Ti and Cr. In some embodiments, the at least two transition metals are Sc and Cr.
[0051] In some embodiments, the ternary alloy nanoparticle catalyst is supported on a refractory oxide support selected from silica, delta-alumina, theta-alumina, gamma-alumina, Si-doped alumina, alkaline earth metal stabilized alumina, transition metal stabilized alumina, zirconium oxide and titania. In some embodiments, the refractory oxide support is silica. In some embodiments, the refractory oxide support is delta-alumina. In some embodiments, the refractory oxide support is theta-alumina. In some embodiments, the refractory oxide support is gamma-alumina. In some embodiments, the refractory oxide support is Si-doped alumina. In some embodiments, the Si-doped alumina contains SiO2 in the range of about 1% to about 20%. In some embodiments, the Si-doped alumina contains about 1% SiO2. In some embodiments, the Si-doped alumina contains about 5% SiO2. In some embodiments, the Si-doped alumina contains about 10% SiO2. In some embodiments, the Si-doped alumina contains about 15% SiO2. In some embodiments, the Si-doped alumina contains about 20% SiO2. In some embodiments, the refractory oxide support is an alkaline earth stabilized alumina. In some embodiments, the alkaline earth stabilized alumina is a Mn stabilized alumina. In some embodiments, the refractory oxide support is a transition metal stabilized alumina. In some embodiments, the transition metal stabilized alumina is a Zr-doped alumina. In some embodiments, the transition metal stabilized alumina is a Ti-doped alumina. In some embodiments, the refractory oxide support is zirconia. In some embodiments, the refractory oxide support is titania.
[0052] In some embodiments, the platinum group metal content of the ternary alloy nanoparticle catalyst is less than or equal to about 80 atomic % of the metal content. In some embodiments, the platinum group metal content is about 20 atomic % of the metal content. In some embodiments, the platinum group metal content is about 25 atomic % of the metal content. In some embodiments, the platinum group metal content is about 30 atomic % of the metal content. In some embodiments, the platinum group metal content is about 35 atomic % of the metal content. In some embodiments, the platinum group metal content is about 40 atomic % of the metal content. In some embodiments, the platinum group metal content is about 45 atomic % of the metal content. In some embodiments, the platinum group metal content is about 50 atomic % of the metal content. In some embodiments, the platinum group metal content is about 55 atomic % of the metal content. In some embodiments, the platinum group metal content is about 60 atomic % of the metal content. In some embodiments, the platinum group metal content is about 65 atomic % of the metal content. In some embodiments, the platinum group metal content is about 70 atomic % of the metal content. In some embodiments, the platinum group metal content is about 75 atomic % of the metal content. In some embodiments, the platinum group metal content is about 80 atomic % of the metal content.
[0053] In some embodiments, the platinum group metal ratio of the ternary alloy nanoparticle catalyst is about 30 atomic % to about 50 atomic % of the metal content. In some embodiments, the weight ratio of the platinum group metal is about 30 atomic % of the metal content. In some embodiments, the weight ratio of the platinum group metal is about 35 atomic % of the metal content. In some embodiments, the weight ratio of the platinum group metal is about 40 atomic % of the metal content. In some embodiments, the weight ratio of the platinum group metal is about 45 atomic % of the metal content. In some embodiments, the weight ratio of the platinum group metal is about 50 atomic % of the metal content.
[0054] In some embodiments, at least two transition metal elements of the ternary alloy nanoparticle catalyst have a combined ratio of about 20 atomic % to about 80 atomic % of metal content. In some embodiments, the combined weight ratio of the at least two transition metal elements is about 20 atomic % of metal content. In some embodiments, the combined weight ratio of the at least two transition metal elements is about 25 atomic % of metal content. In some embodiments, the combined weight ratio of the at least two transition metal elements is about 30 atomic % of metal content. In some embodiments, the combined weight ratio of the at least two transition metal elements is about 35 atomic % of metal content. In some embodiments, the combined weight ratio of the at least two transition metal elements is about 40 atomic % of metal content. In some embodiments, the combined weight ratio of the at least two transition metal elements is about 45 atomic % of metal content. In some embodiments, the combined weight ratio of the at least two transition metal elements is about 50 atomic % of metal content. In some embodiments, the combined weight ratio of the at least two transition metal elements is about 55 atomic % of metal content. In some embodiments, the combined weight ratio of the at least two transition metal elements is about 60 atomic % of metal content. In some embodiments, the combined weight ratio of the at least two transition metal elements is about 65 atomic % of the metal content. In some embodiments, the combined weight ratio of the at least two transition metal elements is about 70 atomic % of the metal content. In some embodiments, the combined weight ratio of the at least two transition metal elements is about 75 atomic % of the metal content. In some embodiments, the combined weight ratio of the at least two transition metal elements is about 80 atomic % of the metal content.
[0055] In some embodiments, the platinum group metal and at least two transition metal elements of the ternary alloy nanoparticle catalyst can be detected by TEM / EDS. In some embodiments, the platinum group metal and at least two transition metal elements of the ternary alloy nanoparticle catalyst can be detected by X-ray diffraction. In some embodiments, after incorporating different levels of at least two transition metals, XRD shows that the 2θ value of Pt fcc (111) is in the range of about 39.7° to about 42°.
[0056] In some embodiments, the ternary alloy nanoparticle catalyst is PtNiCo. In some embodiments, the atomic ratio of the PtNiCo ternary alloy nanoparticle catalyst is about 20%-80% Pt, about 1%-50% Ni, and about 5%-40% Co. In some embodiments, the atomic ratio is about 30%-60% Pt, about 20%-40% Ni, and about 10%-30% Co.
[0057] In some embodiments, the ternary alloy nanoparticle catalyst is PtMnFe. In some embodiments, the atomic ratio of the PtMnFe ternary alloy nanoparticle catalyst is about 15%-40% Pt, about 10%-50% Mn, and about 10%-50% Fe. In some embodiments, the atomic ratio is about 30%-40% Pt, about 30%-40% Mn, and about 30%-40% Fe.
[0058] In some embodiments, an oxidation catalyst composite for reducing exhaust emissions of a lean-burn engine is provided, comprising the above-mentioned ternary alloy nanoparticle catalyst. In some embodiments, the lean-burn engine is a lean-burn gasoline engine or a diesel engine, preferably a diesel engine.
[0059] In some embodiments, the oxidation catalyst composite comprises:
[0060] a carrier substrate having a length, an inlet end, and an outlet end, and
[0061] an oxidation catalyst catalytic material, the oxidation catalyst catalytic material comprising the ternary alloy nanoparticle catalyst,
[0062] The oxidation catalyst catalytic material is disposed on the carrier substrate.
[0063] In some embodiments, the oxidation catalyst catalytic material comprises, preferably consists of, a washcoat layer comprising a ternary alloy nanoparticle catalyst. In some embodiments, the washcoat layer comprises a zeolite.
[0064] In some embodiments, the washcoat comprises 5 g / ft 2 of the ternary alloy nanoparticle catalyst, calculated as an element. 3 Up to 500g / ft 3 of platinum group metals, preferably 10 g / ft 3 Up to 300g / ft 3 , more preferably 20g / ft 3 Up to 200g / ft 3 , more preferably 40g / ft 3 Up to 150g / ft 3 , more preferably 60g / ft 3 Up to 120g / ft 3 , more preferably 80g / ft 3 Up to 100g / ft 3In some embodiments, the oxidation catalyst catalytic material comprises, preferably consists of, a bottom washcoat and a top washcoat, wherein the bottom washcoat is disposed on a carrier substrate and the top washcoat is disposed on the bottom washcoat. In some embodiments, the bottom washcoat, the top washcoat, or both the bottom washcoat and the top washcoat comprise a ternary alloy nanoparticle catalyst.
[0065] In some embodiments, the bottom washcoat layer or the top washcoat layer comprises a ternary alloy nanoparticle catalyst, wherein the bottom washcoat layer or the top washcoat layer comprises 5 g / ft 2 of the ternary alloy nanoparticle catalyst, calculated as an element. 3 Up to 500g / ft 3 Platinum group metal (), preferably 10g / ft 3 Up to 300g / ft 3 , more preferably 20g / ft 3 Up to 200g / ft 3 , more preferably 40g / ft 3 Up to 150g / ft 3 , more preferably 60g / ft 3 Up to 120g / ft 3 , more preferably 80g / ft 3 Up to 100g / ft 3 .
[0066] In some embodiments, the bottom washcoat layer and the top washcoat layer comprise a ternary alloy nanoparticle catalyst, wherein the total amount of platinum group metal in the bottom washcoat layer and the top washcoat layer, calculated as an element, from the ternary alloy nanoparticle catalyst contained in the bottom washcoat layer and the top washcoat layer is between 5 g / ft 3 Up to 500g / ft 3 , preferably 10g / ft 3 Up to 300g / ft 3 , more preferably 20g / ft 3 Up to 200g / ft 3 , more preferably 40g / ft 3 Up to 150g / ft 3 , more preferably 60g / ft 3 Up to 120g / ft 3 , more preferably 80g / ft 3 Up to 100g / ft 3 within the range.
[0067] In some embodiments, the top washcoat or the bottom washcoat comprises a zeolite, wherein preferably the top washcoat comprises a zeolite. In some embodiments, the top washcoat comprises a zeolite and the bottom washcoat is substantially free of zeolite. In some embodiments, the bottom washcoat comprises a zeolite and the top washcoat is substantially free of zeolite. Within the meaning of the present invention, "substantially free" means that the washcoat contains less than 1% by weight, preferably less than 0.5% by weight, more preferably less than 0.1% by weight, more preferably less than 0.05% by weight, more preferably less than 0.01% by weight, more preferably less than 0.005% by weight, more preferably less than 0.001% by weight of zeolite.
[0068] In some embodiments, the washcoat or washcoat comprising a ternary alloy nanoparticle catalyst is substantially free of barium, wherein preferably, the washcoat or washcoat comprising a ternary alloy nanoparticle catalyst is substantially free of alkaline earth metals. Within the meaning of the present invention, "substantially free" means that the washcoat contains less than 1 wt% of barium or alkaline earth metals (calculated as the corresponding element), preferably less than 0.5 wt%, more preferably less than 0.1 wt%, more preferably less than 0.05 wt%, more preferably less than 0.01 wt%, more preferably less than 0.005 wt%, more preferably less than 0.001 wt%. In some embodiments, the carrier substrate is a wall-flow substrate or a flow-through substrate, preferably a flow-through substrate, more preferably a honeycomb monolithic substrate.
[0069] The present disclosure also relates to a method for preparing a ternary alloy nanoparticle catalyst, the ternary alloy nanoparticle catalyst comprising a platinum group metal alloyed with at least two transition metal elements. For example, the present disclosure relates to a method for preparing a ternary alloy nanoparticle catalyst, the ternary alloy nanoparticle catalyst comprising a platinum group metal alloyed with at least two transition metal elements, the method comprising: (a) combining a salt of a platinum group metal and a salt of at least two transition metal elements with a capping agent in an organic solvent to form a slurry; (b) introducing a reducing agent into the slurry to produce a colloidal suspension of the ternary alloy nanoparticle catalyst; (c) collecting and adsorbing the ternary alloy nanoparticle catalyst onto a refractory oxide support; and (d) drying and calcining the adsorbed ternary alloy nanoparticle catalyst and the refractory oxide support.
[0070] In some embodiments, the method includes (a) combining a precursor of a platinum group metal and a precursor of two transition metal elements with a capping agent in an organic solvent to form a solution. In some embodiments, the precursor of the platinum group metal is platinum (II) acetylacetonate. In some embodiments, the precursor of the platinum group metal is chloroplatinic acid. In some embodiments, the precursor of the platinum group metal is platinum (II) hydroxysulfite. In some embodiments, the precursor of the platinum group metal is tetraammine platinum (II) chloride. In some embodiments, the precursor of the platinum group metal is tetraammine platinum (II) nitrate. In some embodiments, the precursors of at least two transition metal elements are nickel (II) acetylacetonate and cobalt (III) acetylacetonate. In some embodiments, the capping agent is citric acid. In some embodiments, the capping agent is polyvinyl pyrrolidone. In some embodiments, the capping agent is oleylamine. In some embodiments, the capping agent is oleic acid. In some embodiments, the capping agent is polyethylene glycol.
[0071] In some embodiments, the method includes (b) introducing a reducing agent into the solution to produce a colloidal suspension of the ternary alloy nanoparticle catalyst. In some embodiments, the reducing agent is sodium borohydride. In some embodiments, the reducing agent is hydrazine. In some embodiments, the reducing agent is formic acid. In some embodiments, the reducing agent is sodium formate. In some embodiments, the reducing agent is an amine-borane complex. In some embodiments, the reducing agent is 1,2-hexadecanediol. In some embodiments, the reducing agent is oleylamine.
[0072] In some embodiments, the method includes (c) collecting the ternary alloy nanoparticle catalyst and adsorbing it onto a refractory oxide support. In some embodiments, the method includes (d) drying and calcining the adsorbed ternary alloy nanoparticle catalyst and the refractory oxide support. In some embodiments, the calcining step includes calcining the ternary alloy nanoparticle catalyst and the refractory oxide support at about 800° C. under a hydrogen atmosphere for about 2 hours, followed by heating at about 260° C. in air for about 1 hour, and heating at about 590° C. in air for about 1 hour.
[0073] In some embodiments, when supported on an inorganic refractory oxide, the nanoparticles of the ternary alloy nanoparticle catalyst have an average particle size of about 2nm to about 10nm. In some embodiments, the nanoparticles of the ternary alloy nanoparticle catalyst have an average particle size of about 2nm to about 5nm. In some embodiments, the nanoparticles have an average particle size of about 2nm. In some embodiments, the nanoparticles have an average particle size of about 3nm. In some embodiments, the nanoparticles have an average particle size of about 4nm. In some embodiments, the nanoparticles have an average particle size of about 5nm.
[0074] As used herein, the term "particle size" refers to the minimum diameter sphere that will completely surround a particle, and the measurement involves a single particle, rather than an agglomeration of two or more particles. Particle size can be measured by laser scattering techniques, using a dispersion or dry powder, such as according to ASTM method D4464. The particle size of submicron-sized particles can also be measured by scanning electron microscopy (SEM) or transmission electron microscopy (TEM), or the particle size of particles (micrometer size) containing a support can be measured by a particle size analyzer. In addition to TEM, carbon monoxide (CO) chemical adsorption can be used to determine the average PGM particle size. This technology does not distinguish between various PGM materials (e.g., Pt, Pd, etc., compared with XRD, TEM and SEM) and only determines the average particle size.
[0075] In some embodiments, the total platinum group metal content of the ternary alloy nanoparticle catalyst is about 0.1% to about 5% by weight of the metal content. In some embodiments, the total platinum group metal content of the ternary alloy nanoparticle catalyst is about 0.5% to about 2% by weight of the metal content. In some embodiments, the total platinum group metal content is about 0.5% by weight of the metal content. In some embodiments, the total platinum group metal content is about 1.0% by weight of the metal content. In some embodiments, the total platinum group metal content is about 1.5% by weight of the metal content. In some embodiments, the total platinum group metal content is about 2% by weight of the metal content. In some embodiments, the total platinum group metal content is about 2.5% by weight of the metal content. In some embodiments, the total platinum group metal content is about 3% by weight of the metal content. In some embodiments, the total platinum group metal content is about 3.5% by weight of the metal content. In some embodiments, the total platinum group metal content is about 4% by weight of the metal content. In some embodiments, the total platinum group metal content is about 4.5% by weight of the metal content. In some embodiments, the total platinum group metal content is about 5% by weight of the metal content.
[0076] In another aspect of the present disclosure, an exhaust treatment system is provided, the exhaust treatment system comprising a ternary alloy nanoparticle catalyst according to any of the preceding embodiments, the catalyst being positioned downstream of and in fluid communication with an internal combustion engine.
[0077] In some embodiments, the internal combustion engine is a lean burn engine, preferably a lean burn gasoline engine or a diesel engine, preferably a diesel engine.In some embodiments, the exhaust treatment system is in fluid communication with the internal combustion engine via an exhaust conduit.
[0078] In some embodiments, the exhaust treatment system further comprises a catalyzed soot filter and / or an SCR catalyst component comprising an SCR catalyst composition, preferably a catalyzed soot filter and an SCR catalyst component comprising an SCR catalyst composition.
[0079] In some embodiments, the catalyzed soot filter and / or SCR catalyst component are located downstream of the ternary alloy nanoparticle catalyst, preferably the oxidation catalyst composite, wherein more preferably, both the catalyzed soot filter and the SCR catalyst component are located downstream of the ternary alloy nanoparticle catalyst, preferably the oxidation catalyst composite.
[0080] In another aspect of the present disclosure, there is provided a method for treating a gas containing hydrocarbons and / or carbon monoxide and / or NO x A method for treating an exhaust gas stream, the method comprising passing the exhaust gas stream through a ternary alloy nanoparticle catalyst or an exhaust gas treatment system according to any of the preceding embodiments. Example
[0081] Comparative Example 1:
[0082] A Pt reference sample was prepared by incipient wetness impregnation. A support material such as alumina was impregnated with a Pt ammine precursor solution followed by drying at 110°C and calcination at 590°C.
[0083] Comparative Example 2:
[0084] A Pt reference sample was prepared in a similar manner to Comparative Example 1, except that a colloidal Pt precursor having an average Pt particle size of 1 nm to 3 nm was used.
[0085] Example 1
[0086] The synthesis of PtNiCo nanoparticles (NPs) involves the reduction and decomposition of three metal precursors, namely, Pt II (acac)2, Ni II (acac)2 and Co III (acac)3. In order to synthesize Pt 41 Ni 36 Co 23 Nanoparticles, 397mg Pt II (acac)2, 256mg Ni II (acac)2 and 356mg Co III(acac)3 was dissolved in 100 ml of dioctyl ether, followed by the addition of 1.0 ml of oleylamine, 1.0 ml of oleic acid and 1.000 g of 1,2-hexadecanediol. The mixture was purged with N2 gas to remove ambient air, and the temperature was then increased in stages to 105°C for 20 minutes, and then to 180°C for 20 minutes until the mixture completely turned dark brown. The temperature was finally increased to 270°C and refluxed for 40 minutes. After cooling to room temperature, the resulting solution was diluted with ethanol in a volume ratio of 1:2.5. After crystallization overnight (~12 hours), the supernatant was discarded and the remaining precipitate was dried by purging with N2 gas for 10 minutes. The precipitated black powder was redispersed in a hexane solution before further use.
[0087] Comparative Example 3
[0088] Colloidal Pt was prepared in a similar manner as used in Example 1. 51 Ni 49 The solution was different from that without adding Co precursor.
[0089] Comparative Example 4
[0090] Colloidal Pt was prepared in a similar manner as used in Example 1. 62 Co 38 solution, except that no Ni precursor was added.
[0091] Example 2
[0092] Colloidal Pt was prepared in a similar manner as used in Example 1. 33 Mn 34 Fe 33 solution, and Pt II (acac)2, Mn2(CO) 10 and Fe(CO)5 are precursors used in a controlled molar ratio.
[0093] Comparative Example 5
[0094] Preparation of Pt via a one-pot synthesis 46 Mn 54 / Al2O3 sample. First, a controlled molar ratio of Pt II (acac)2 and Mn II (acac)2 and Al2O3 support were suspended in DMF solvent and then transferred to a Teflon autoclave for 12 hours of reaction. The resulting powder was washed with ethanol and filtered, and then calcined at 590°C in air for one hour.
[0095] Example 3
[0096] Supported PtNiCo on alumina was prepared by adding the colloidal PtNiCo solution of Example 1 (10 mg / mL to 20 mg / mL hexane) to an inorganic support material (0.5 g to 10 g) suspended in 5 mL to 30 mL of a premixed isopropanol / hexane (1:9 volume ratio) solution. The mixture was sonicated for 20 minutes and then purged with N2 to remove the solvent. The dried fine powder was then calcined at 800°C for 2 hours under a H2 atmosphere, followed by continuous calcination at 260°C for 1 hour in air, and then calcined again at 590°C for 1 hour. This protocol resulted in all samples maintaining almost the same trimetallic composition, with Pt% enrichment slightly higher than the nanoparticle precursor.
[0097] Comparative Example 6
[0098] Supported Pt was prepared in a similar manner as used in Example 3. 51 Ni 49 / Al2O3 catalyst, except that the colloidal PtNi solution of Comparative Example 3 was used.
[0099] Comparative Example 7
[0100] Supported Pt was prepared in a similar manner as used in Example 3. 63 Co 37 / Al2O3 catalyst, except that the colloidal PtCo solution of Comparative Example 4 was used.
[0101] Example 4
[0102] Supported Pt was prepared in a similar manner as used in Example 3. 37 Mn 50 Fe 13 / Al2O3 catalyst, except that the colloidal PtMnFe solution of Example 2 was used.
[0103] Example 5 (High Throughput Powder Test)
[0104] The powder catalyst was crushed and sieved to 250-500 μm size range, and 100 mg was diluted to ~1 mL volume with corundum. The sample was loaded on a high throughput test unit, and each sample was tested at 125°C, 135°C, 150°C, 165°C, 180°C, 195°C, 210°C, 225°C, 250°C and 300°C. The feed gas composition was 500 ppm NO, 300 ppm CO, 40 ppm propylene, 60 ppm-C1HC (toluene / decane=1 / 2, based on C1), 10% O2, 10% CO2 and 10% H2O, and the space velocity (simulating the catalyst of 1 mL coating) was 45000 / h.
[0105] Example 6 (single powder test)
[0106] The powder catalyst was sieved to 200-500 μm and 30 mg sample was tested in a simulated exhaust gas mixture (200 ppm NO + 167 ppm C3H6 + 333 ppm CO + 10% O2 + 10% H2O + N2 balance) at a flow rate of 250 ml / min.
[0107] Figure 1 The synthesized PtNiCo[( Figure 1 A) and ( Figure 1 D)]、PtNi( Figure 1 B) and PtCo( Figure 1 C) Comparison of the particle size of nanoparticles. Ternary alloy example 1 (Pt 41 Ni 36 Co 23 ) showed a minimum average grain size of 2.9 nm to 3.6 nm. 45 Ni 55 ) and Comparative Example 4 (Pt 63 Co 37 ) have a particle size of 9 nm to 10 nm and 4 nm to 5 nm, respectively. Once deposited on alumina [Example 3, Pt 41 Ni 36 Co 23 / Al2O3( Figure 1 D)], some larger PtNiCo nanoparticles will appear, and the particle size range increases to 2nm to 10nm.
[0108] Figure 2 The effect of the Pt / Mn / Fe ratio on the nanoparticle size is shown. 13 Mn 27 Fe 60 NPs( Figure 2 A) shows a mixture of small particles with an average particle size of 2.8 ± 0.6 nm and large nanoparticles with a diameter of 6.4 ± 1.7 nm. Figure 2 B shows Pt with an average particle size of about 4.0 ± 0.5 nm 38 Mn 29 Fe 33 Representative images of nanoparticles. Figure 2 C, Pt 86 Mn1Fe 13 The average particle size of the nanoparticles was estimated to be -6.1 ± 1.0 nm. These results indicate that particle size and morphology are highly dependent on metal composition. The smallest particles occur at an intermediate Pt level of -40 atomic % Pt. Figure 2D shows Al2O3 supported Pt 38 Mn 29 Fe 33 The particle size of the alloy particles, estimated to be -4.2 ± 0.7 nm, indicates that neither the original Pt / Mn / Fe ratio nor the particle size was changed upon deposition onto alumina.
[0109] Figure 3 The X-ray diffraction pattern of Example 1 (isolated PtNiCo nanoparticles) is shown, in which the broad peak at about 41.4° is attributed to Pt (111), which has shifted from 39.7° for pure Pt as a result of alloying with Ni and Co. When equal weight % Pt is dispersed on alumina, Example 3 (PtNiCo / Al2O3) shows a Pt (111) peak at 40.8°, while Example 1 is at 39.9°, indicating that the alloy structure of the PtNiCo particles remains unchanged.
[0110] Despite Figure 1 The EDS mapping of fresh Example 3 in D shows that Ni and Co are enriched on the Pt particles, but the resolution is severely limited due to the small particle size and low concentration of Ni and Co. In Example 3 aged at 650°C / 50h, the tight association of Pt-Ni-Co is more easily confirmed. Figure 4 Elemental line profiles across two PtNiCo particles (Particle A and Particle B) are shown as indicated by the arrow lines in the TEM image. Each particle is now dominated by the Pt signal, with Ni and Co signals consistently observed across the particle, but at levels significantly lower than the original PtNiCo nanoparticles (Pt 41 Ni 36 Co 23 ). The atomic ratio of particle A now becomes Pt 96.34 / Ni 0.56 / Co 3.10 , the atomic ratio of particle B becomes Pt 95.90 / Ni 1.95 / Co 2.16 . This observation suggests that a large amount of Ni / Co is separated from Pt during aging and may be dispersed into the alumina support. The remaining trace amounts of Ni and Co may continue to play a key role in modifying the Pt chemistry. Ni and Co are oxophilic, and at the particle-support interface, they can help anchor the ternary alloy particles more firmly to the support and slow down aging; on the particle surface, Ni and Co can promote the activation of O2 and enhance the oxidation reaction.
[0111] Figure 5The activity of Example 3 and Comparative Example 1 in oxidation of NO to NO2 before and after aging was compared. Although Example 3 showed lower activity in the fresh state, it remained stable after 650°C / 50h HT aging compared to the reference (i.e. Comparative Example 1).
[0112] Figure 6 The higher stability of Example 3 is clearly demonstrated in Figure 2, where the NO2 / NO2 ratio from fresh catalyst to aged catalyst at 210°C, 225°C and 250°C is compared. x ratio. At each temperature, Example 3 showed significantly less activity decay due to aging. The greatest deactivation was observed in Comparative Example 2 using a colloidal Pt precursor. Despite the significant changes in the Pt / Ni / Co ratio and particle sintering after aging, Example 3 largely maintained its NO oxidation activity, implying that the remaining small amounts of Ni and Co play an important role in enhancing NO oxidation. On the other hand, Example 3 showed similar CO and HC ignition activities to Comparative Examples 1 and 2, except that a higher CO ignition activity was observed for fresh Example 3, as shown in FIG. Figure 7 It appears that the presence of Ni / Co in Pt has the greatest impact on maintaining NO oxidation activity after hydrothermal aging.
[0113] Figure 8 and Fig. 9 The effect of Pt atomic ratio on NO2 generation stability from fresh to aged is shown in Example 3. Here, the highest stability is obtained around the intermediate Pt level -41%. The amount of Ni may also be a consideration, as high stability is observed when Ni is present in similar molar amounts to Co.
[0114] Fig.10 A comparison of the activities of the bimetallic alloys PtNi (Comparative Example 6) and PtCo (Comparative Example 7) supported on alumina is shown. While Comparative Example 6 shows similar activity to Comparative Example 1, Comparative Example 7 shows extremely high fresh activity but a severe drop in activity after aging. Thus, the ternary alloy PtNiCo has a mechanism for enhanced NO oxidation that the bimetallic alloy cannot achieve.
[0115] Fig.11 Example 4 (Pt 37 Mn 50 Fe 13 Example 4 shows a comparison of the activity of Pt / Al2O3) with that of Comparative Example 1. Example 4 shows lower NO oxidation activity in the fresh state, and after aging the activity drops to a level similar to that of Comparative Example 1. Characterization data (TEM and EDS) show that significant phase separation occurs after aging, resulting in the separation of Mn and Fe from the Pt particles and integration into the alumina support.
[0116] Fig.12 A comparison of the fresh activity of bimetallic PtMn alloy particles supported on alumina (Comparative Example 5) and Comparative Example 1 is shown. It appears that the presence of Mn alone in the alloy significantly reduces the NO oxidation activity. Based on the fact that the ternary Pt alloy samples tend to provide better or equal NO2 stability, it is suggested that the negative impact of a single transition metal is significantly altered in the presence of a second transition metal, leading to enhanced activity, especially in the case of the PtNiCo catalyst.
[0117] DRIFTS (diffuse reflectance infrared Fourier transform spectroscopy) studies of CO adsorption experiments of Comparative Examples and Example 3 show that before aging, both Comparative Examples have a higher Pt surface available for CO adsorption than Example 3. This may be due to two factors: (1) the PtNiCo alloy nanoparticle precursor has a larger average particle size compared to the initial Pt particles obtained in the Comparative Examples; (2) it is also found that the ternary PtNiCo alloy nanoparticles are rich in Ni and Co on the surface, which reduces the Pt available on the surface for CO adsorption. After hydrothermal aging at 650°C / 50 hours, although all catalysts show a significant decrease in CO adsorption intensity, the decrease is more significant for Comparative Examples 1 and 2. Example 3 now has the highest Pt surface available for CO adsorption (see Fig.13 ), indicating that Example 3 is more resistant to hydrothermal aging due to the presence of Ni and Co. Ni and Co are oxophilic, which can improve the adhesion of the ternary nano-alloy particles to the inorganic oxide support and thus slow down particle growth and agglomeration. On the surface of the nanoparticles, Ni and Co more effectively activate O2 and promote oxidation reactions.
[0118] Implementation
[0119] The invention is further illustrated by the following set of embodiments and combinations of embodiments resulting from the indicated dependencies and back-references. In particular, it should be noted that in each case where a range of embodiments is mentioned, for example in the context of a term such as "a catalyst according to any one of embodiments 1 to 4", each embodiment within this range is meant to be explicitly disclosed to the skilled person, i.e. the wording of this term should be understood by the skilled person as being synonymous with "a catalyst according to any one of embodiments 1, 2, 3 and 4". Furthermore, it is explicitly noted that the following set of embodiments is not a set of claims determining the degree of protection, but rather represents a properly structured part of a description of general and preferred aspects of the invention.
[0120] 1. A ternary alloy nanoparticle catalyst comprising a platinum group metal alloyed with at least two transition metal elements.
[0121] 2. According to the ternary alloy nanoparticle catalyst described in Embodiment 1, the ternary alloy nanoparticle catalyst comprises two transition metal elements.
[0122] 3. According to the ternary alloy nanoparticle catalyst described in Embodiment 1, the ternary alloy nanoparticle catalyst comprises three transition metal elements.
[0123] 4. The ternary alloy nanoparticle catalyst according to Embodiment 1, wherein the ternary alloy nanoparticle catalyst comprises four transition metal elements.
[0124] 5. The ternary alloy nanoparticle catalyst according to any one of embodiments 1 to 4, wherein the platinum group metal is selected from Pt, Pd, Ru, Rh, Ir and Os.
[0125] 6. The ternary alloy nanoparticle catalyst according to any one of embodiments 1 to 5, wherein the platinum group metal is selected from Pt, Pd and Ru.
[0126] 7. The ternary alloy nanoparticle catalyst according to any one of embodiments 1 to 6, wherein the platinum group metal is selected from Pt and Pd.
[0127] 8. The ternary alloy nanoparticle catalyst according to any one of embodiments 1 to 7, wherein the platinum group metal is a combination of Pt and Pd.
[0128] 9. The ternary alloy nanoparticle catalyst according to any one of embodiments 1 to 7, wherein the platinum group metal is Pt.
[0129] 10. The ternary alloy nanoparticle catalyst according to any one of embodiments 1 to 9, wherein the at least two transition metal elements are selected from Ni, Co, Mn, Fe, V, Zn, Cu, Ti, Sc and Cr.
[0130] 11. The ternary alloy nanoparticle catalyst according to any one of embodiments 1 to 10, wherein the at least two transition metal elements are selected from Ni, Co, Mn and Fe.
[0131] 12. The ternary alloy nanoparticle catalyst according to any one of embodiments 1 to 11, wherein the at least two transition metal elements are Ni and Co.
[0132] 13. The ternary alloy nanoparticle catalyst according to any one of embodiments 1 to 11, wherein the at least two transition metal elements are Mn and Fe.
[0133] 14. A ternary alloy nanoparticle catalyst according to any one of embodiments 1 to 13, wherein the ternary alloy nanoparticles are supported on a refractory oxide carrier, and the refractory oxide carrier is selected from silica, δ-alumina, θ-alumina, γ-alumina, Si-doped alumina, alkaline earth metal stabilized alumina, transition metal stabilized alumina, zirconium oxide and titanium dioxide.
[0134] 15. The ternary alloy nanoparticle catalyst according to embodiment 14, wherein the refractory oxide support is Si-doped alumina containing SiO2 in a range of about 1% to about 20%.
[0135] 16. The ternary alloy nanoparticle catalyst according to embodiment 14, wherein the refractory oxide support is Mn-stabilized alumina.
[0136] 17. The ternary alloy nanoparticle catalyst according to embodiment 14, wherein the refractory oxide support is Zr-doped alumina.
[0137] 18. The ternary alloy nanoparticle catalyst according to embodiment 14, wherein the refractory oxide support is Ti-doped alumina.
[0138] 19. The ternary alloy nanoparticle catalyst of any one of embodiments 1 to 18, wherein the platinum group metal content of the alloy is less than or equal to about 80 atomic % of the metal content.
[0139] 20. The ternary alloy nanoparticle catalyst of any one of embodiments 1 to 19, wherein the platinum group metal content of the alloy is about 80 atomic % of the metal content.
[0140] 21. The ternary alloy nanoparticle catalyst of any one of embodiments 1 to 19, wherein the platinum group metal content of the alloy is about 70 atomic % of the metal content.
[0141] 22. The ternary alloy nanoparticle catalyst according to any one of embodiments 1 to 19, wherein the weight ratio of the platinum group metal is about 60 atomic % of the metal content.
[0142] 23. The ternary alloy nanoparticle catalyst of any one of embodiments 1 to 19, wherein the platinum group metal content of the alloy is about 50 atomic % of the metal content.
[0143] 24. The ternary alloy nanoparticle catalyst of any one of embodiments 1 to 19, wherein the platinum group metal content of the alloy is about 40 atomic % of the metal content.
[0144] 25. The ternary alloy nanoparticle catalyst according to any one of embodiments 1 to 19, wherein the weight ratio of the platinum group metal is about 30 atomic % of the metal content.
[0145] 26. The ternary alloy nanoparticle catalyst of any one of embodiments 1 to 19, wherein the platinum group metal content of the alloy is about 20 atomic % of the metal content.
[0146] 27. The ternary alloy nanoparticle catalyst according to any one of embodiments 1 to 26, wherein the combined weight ratio of the at least two transition metal elements is from about 20 atomic % to about 80 atomic % of the metal content.
[0147] 28. The ternary alloy nanoparticle catalyst according to any one of embodiments 1 to 27, wherein the combined weight ratio of the at least two transition metal elements is about 20 atomic % of the metal content.
[0148] 29. The ternary alloy nanoparticle catalyst according to any one of embodiments 1 to 27, wherein the combined weight ratio of the at least two transition metal elements is about 30 atomic % of the metal content.
[0149] 30. The ternary alloy nanoparticle catalyst according to any one of embodiments 1 to 27, wherein the combined weight ratio of the at least two transition metal elements is about 40 atomic % of the metal content.
[0150] 31. The ternary alloy nanoparticle catalyst according to any one of embodiments 1 to 27, wherein the combined weight ratio of the at least two transition metal elements is about 50 atomic % of the metal content.
[0151] 32. The ternary alloy nanoparticle catalyst according to any one of embodiments 1 to 27, wherein the combined weight ratio of the at least two transition metal elements is about 60 atomic % of the metal content.
[0152] 33. The ternary alloy nanoparticle catalyst according to any one of embodiments 1 to 27, wherein the combined weight ratio of the at least two transition metal elements is about 70 atomic % of the metal content.
[0153] 34. The ternary alloy nanoparticle catalyst according to any one of embodiments 1 to 27, wherein the combined weight ratio of the at least two transition metal elements is about 80 atomic % of the metal content.
[0154] 35. The ternary alloy nanoparticle catalyst according to any one of embodiments 1 to 34, wherein the platinum group metal and the at least two transition metal elements can be detected by TEM / EDS (transmission electron microscopy combined with energy dispersive X-ray spectroscopy), X-ray diffraction, or a combination thereof.
[0155] 36. The ternary alloy nanoparticle catalyst according to any one of embodiments 1 to 35, wherein after incorporation of different levels of the at least two transition metals, the XRD exhibits a 2θ value of Pt fcc (111) in the range of about 39.7° to about 42°.
[0156] 37. The ternary alloy nanoparticle catalyst according to any one of embodiments 1 to 36, wherein the ternary alloy nanoparticle catalyst is PtNiCo.
[0157] 38. The ternary alloy nanoparticle catalyst according to embodiment 37, wherein the atomic ratio of the PtNiCo ternary alloy nanoparticle catalyst is 20%-80% Pt, 1%-50% Ni and 5%-40% Co.
[0158] 39. The ternary alloy nanoparticle catalyst according to embodiment 37, wherein the atomic ratio of the PtNiCo ternary alloy nanoparticle catalyst is 30%-60% Pt, 20%-40% Ni and 10%-30% Co.
[0159] 40. The ternary alloy nanoparticle catalyst according to any one of embodiments 1 to 36, wherein the ternary alloy nanoparticle catalyst is PtMnFe.
[0160] 41. The ternary alloy nanoparticle catalyst according to embodiment 40, wherein the atomic ratio of the PtMnFe ternary alloy nanoparticle catalyst is 15%-40% Pt, 10%-50% Mn and 10%-50% Fe.
[0161] 42. The ternary alloy nanoparticle catalyst according to embodiment 40, wherein the atomic ratio of the PtMnFe ternary alloy nanoparticle catalyst is 30%-40% Pt, 30%-40% Mn and 30%-40% Fe.
[0162] 43. An oxidation catalyst composite for reducing exhaust emissions from a lean-burn engine, the oxidation catalyst composite comprising a ternary alloy nanoparticle catalyst according to any one of embodiments 1 to 42, wherein preferably the lean-burn engine is a lean-burn gasoline engine or a diesel engine, more preferably a diesel engine.
[0163] 44. The oxidation catalyst composite of embodiment 43, wherein the oxidation catalyst composite comprises:
[0164] a carrier substrate having a length, an inlet end, and an outlet end, and
[0165] an oxidation catalyst catalytic material, wherein the oxidation catalyst catalytic material comprises the ternary alloy nanoparticle catalyst,
[0166] The oxidation catalyst catalytic material is disposed on the carrier substrate.
[0167] 45. An oxidation catalyst composite according to embodiment 44, wherein the oxidation catalyst catalytic material includes, preferably consists of, a washcoat layer, and the washcoat layer contains the ternary alloy nanoparticle catalyst.
[0168] 46. An oxidation catalyst composite according to embodiment 45, wherein the washcoat layer comprises zeolite.
[0169] 47. The oxidation catalyst composite of embodiment 45 or 46, wherein the washcoat layer comprises 5 g / ft 2 of the ternary alloy nanoparticles, calculated as elements. 3 Up to 500g / ft 3 of platinum group metals, preferably 10 g / ft 3 Up to 300g / ft 3 , more preferably 20g / ft 3 Up to 200g / ft 3 , more preferably 40g / ft 3 Up to 150g / ft 3 , more preferably 60g / ft 3 Up to 120g / ft 3 , more preferably 80g / ft 3 Up to 100g / ft 3 .
[0170] 48. An oxidation catalyst composite according to embodiment 44, wherein the oxidation catalyst catalytic material includes a bottom repair substrate coating and a top repair substrate coating, preferably consisting of the bottom repair substrate coating and the top repair substrate coating, wherein the bottom repair substrate coating is arranged on the carrier substrate, and the top repair substrate coating is arranged on the bottom repair substrate coating.
[0171] 49. An oxidation catalyst composite according to embodiment 48, wherein the bottom washcoat layer, the top washcoat layer, or both the bottom washcoat layer and the top washcoat layer comprise the ternary alloy nanoparticle catalyst.
[0172] 50. The oxidation catalyst composite of embodiment 49, wherein the bottom washcoat layer or the top washcoat layer comprises the ternary alloy nanoparticle catalyst, wherein the bottom washcoat layer or the top washcoat layer comprises 5 g / ft 2 of the ternary alloy nanoparticle catalyst, calculated as an element. 3 Up to 500g / ft 3 of platinum group metals, preferably 10 g / ft 3 Up to 300g / ft 3 , more preferably 20g / ft 3 Up to 200g / ft 3 , more preferably 40g / ft 3 Up to 150g / ft 3 , more preferably 60g / ft 3 Up to 120g / ft 3 , more preferably 80g / ft 3 Up to 100g / ft 3 .
[0173] 51. An oxidation catalyst composite according to embodiment 49, wherein the bottom washcoat layer and the top washcoat layer comprise the ternary alloy nanoparticle catalyst, wherein the total amount of platinum group metal in the bottom washcoat layer and the top washcoat layer calculated as an element from the ternary alloy nanoparticle catalyst contained in the bottom washcoat layer and the top washcoat layer is within 5 g / ft 3 Up to 500g / ft 3 , preferably 10g / ft 3 Up to 300g / ft 3 , more preferably 20g / ft 3 Up to 200g / ft 3 , more preferably 40g / ft 3 Up to 150g / ft 3 , more preferably 60g / ft 3 Up to 120g / ft 3 , more preferably 80g / ft 3 Up to 100g / ft 3 within the range.
[0174] 52. An oxidation catalyst composite according to any one of embodiments 48 to 51, wherein the top washcoat layer or the bottom washcoat layer comprises a zeolite, wherein preferably the top washcoat layer comprises a zeolite.
[0175] 53. An oxidation catalyst composite according to embodiment 52, wherein the top washcoat layer comprises zeolite and the bottom washcoat layer is substantially free of zeolite.
[0176] 54. An oxidation catalyst composite according to embodiment 52, wherein the bottom washcoat layer comprises zeolite and the top washcoat layer is substantially free of zeolite.
[0177] 55. An oxidative catalyst composite according to any one of embodiments 45 to 54, wherein one or more of the repair substrate coatings comprising the ternary alloy nanoparticle catalyst are substantially free of barium, wherein preferably one or more of the repair substrate coatings comprising the ternary alloy nanoparticle catalyst are substantially free of alkaline earth metals.
[0178] 56. An oxidation catalyst composite according to any one of embodiments 44 to 55, wherein the support substrate is a wall-flow substrate or a flow-through substrate, preferably a flow-through substrate, and more preferably a honeycomb monolithic substrate.
[0179] 57. A method for preparing a ternary alloy nanoparticle catalyst comprising a platinum group metal alloyed with at least two transition metal elements, the method comprising:
[0180] (a) combining the precursor of the platinum group metal and the precursor of the at least two transition metal elements with a capping agent in an organic solvent to form a slurry;
[0181] (b) introducing a reducing agent into the solution to produce a colloidal suspension of the ternary alloy nanoparticle catalyst;
[0182] (c) collecting and adsorbing the ternary alloy nanoparticle catalyst onto a refractory oxide support; and
[0183] (d) drying and calcining the adsorbed ternary alloy nanoparticle catalyst and refractory oxide support.
[0184] 58. The method according to embodiment 57, wherein the precursor of the platinum group metal is selected from platinum (II) acetylacetonate, chloroplatinic acid, platinum (II) hydroxysulfite, tetraamine platinum (II) chloride and tetraamine platinum (II) nitrate.
[0185] 59. The method according to embodiment 57 or 58, wherein the precursors of the at least two transition metal elements are selected from nickel (II) acetylacetonate and cobalt (III) acetylacetonate.
[0186] 60. The method of any one of embodiments 57 to 59, wherein the capping agent is selected from citric acid, polyvinyl pyrrolidone, oleylamine, oleic acid, and polyethylene glycol.
[0187] 61. The method of any one of embodiments 57 to 60, wherein the reducing agent is selected from sodium borohydride, hydrazine, formic acid, sodium formate and amine-borane complexes; 1,2-hexadecanediol and oleylamine.
[0188] 62. The method of any one of embodiments 57 to 61, wherein the refractory oxide support is selected from silica, delta-alumina, theta-alumina, gamma-alumina, Si-doped alumina, alkaline earth stabilized alumina, transition metal stabilized alumina, zirconia, and titania.
[0189] 63. A method according to embodiment 62, wherein the refractory oxide support is Si-doped alumina containing SiO2 in the range of about 1% to about 20%.
[0190] 64. The method of embodiment 62, wherein the refractory oxide support is Mn-stabilized alumina.
[0191] 65. The method of embodiment 62, wherein the refractory oxide support is Zr-doped alumina.
[0192] 66. The method of embodiment 62, wherein the refractory oxide support is Ti-doped alumina.
[0193] 67. A method according to any one of embodiments 57 to 66, wherein the calcining step comprises calcining the ternary alloy nanoparticle catalyst and refractory oxide support at about 800°C for about 2 hours under a hydrogen atmosphere, followed by heating at about 260°C for about 1 hour in air, and heating at about 590°C for about 1 hour in air.
[0194] 68. The method of any one of embodiments 57 to 67, wherein the nanoparticles of the ternary alloy nanoparticle catalyst have an average particle size in a range from about 2 nm to about 10 nm.
[0195] 69. The method of any one of embodiments 57 to 67, wherein the nanoparticles of the ternary alloy nanoparticle catalyst have an average particle size in the range of about 2 nm to about 5 nm.
[0196] 70. The method of any one of embodiments 57 to 69, wherein the total platinum group metal content of the ternary alloy nanoparticle catalyst is from about 0.1 wt % to about 5 wt % of the metal content.
[0197] 71. The method of any one of embodiments 57 to 70, wherein the total platinum group metal content of the ternary alloy nanoparticle catalyst is from about 0.5 wt.% to about 2 wt.% of the metal content.
[0198] 72. An exhaust treatment system, comprising a ternary alloy nanoparticle catalyst according to any one of the preceding embodiments, preferably comprising an oxidation catalyst composite according to any one of embodiments 57 to 70, the exhaust treatment system being positioned downstream of an internal combustion engine and being fluidly connected to the internal combustion engine.
[0199] 73. An exhaust treatment system according to embodiment 72, wherein the internal combustion engine is a lean burn engine, preferably a lean burn gasoline engine or a diesel engine, preferably a diesel engine.
[0200] 74. An exhaust treatment system according to embodiment 72 or 73, wherein the exhaust treatment system is connected to the internal combustion engine fluid via an exhaust conduit.
[0201] 75. An exhaust gas treatment system according to any one of embodiments 72 to 74, wherein the exhaust gas treatment system further comprises a catalyzed soot filter and / or an SCR catalyst component containing an SCR catalyst composition, preferably a catalyzed soot filter and an SCR catalyst component containing an SCR catalyst composition.
[0202] 76. An exhaust gas treatment system according to embodiment 75, wherein the catalytic soot filter and / or the SCR catalyst component are located downstream of the ternary alloy nanoparticle catalyst, preferably the oxidation catalyst complex, wherein more preferably, the catalytic soot filter and the SCR catalyst component are both located downstream of the ternary alloy nanoparticle catalyst, preferably the oxidation catalyst complex.
[0203] 77. A method of treating a gas containing hydrocarbons and / or carbon monoxide and / or NO x A method for treating an exhaust gas flow, the method comprising passing the exhaust gas flow through a ternary alloy nanoparticle catalyst according to any one of the preceding embodiments, or through an oxidation catalyst composite according to any one of embodiments 43 to 56, or through an exhaust gas treatment system according to any one of the preceding embodiments.
[0204] 78. The method of embodiment 77, wherein the exhaust gas stream comprises NO x , preferably carbon monoxide and NO x , more preferably hydrocarbons, carbon monoxide and NO x .
[0205] 79. Use of the ternary alloy nanoparticle catalyst according to any one of embodiments 1 to 42, or the oxidation catalyst composite according to any one of embodiments 43 to 56, or the exhaust gas treatment system according to any one of embodiments 72 to 76 for treating exhaust gas from a lean-burn gasoline engine or a diesel engine, preferably a diesel engine.
Claims
1. A ternary alloy nanoparticle catalyst comprising a platinum group metal alloyed with at least two transition metal elements.
2. The ternary alloy nanoparticle catalyst according to claim 1, wherein the platinum group metal is selected from the group consisting of Pt, Pd, Ru, Rh, Ir and Os.
3. The ternary alloy nanoparticle catalyst according to claim 1 or 2, wherein the at least two transition metal elements are selected from Ni, Co, Mn, Fe, V, Zn, Cu, Ti, Sc and Cr.
4. The ternary alloy nanoparticle catalyst according to any one of claims 1 to 3, wherein the ternary alloy nanoparticles are supported on a refractory oxide carrier, and the refractory oxide carrier is selected from silica, δ-alumina, θ-alumina, γ-alumina, Si-doped alumina, alkaline earth metal stabilized alumina, transition metal stabilized alumina, zirconia and titania.
5. The ternary alloy nanoparticle catalyst according to any one of claims 1 to 4, wherein the platinum group metal content of the alloy is less than or equal to about 80 atomic % of the metal content.
6. The ternary alloy nanoparticle catalyst according to any one of claims 1 to 5, wherein the weight ratio of the platinum group metal is from about 30 atomic % to about 50 atomic % of the metal content.
7. The ternary alloy nanoparticle catalyst according to any one of claims 1 to 6, wherein a combined ratio of the at least two transition metal elements is from about 20 atomic % to about 80 atomic % of the metal content.
8. The ternary alloy nanoparticle catalyst according to any one of claims 1 to 7, wherein the platinum group metal and the at least two transition metal elements can be detected by TEM / EDS (transmission electron microscopy combined with energy dispersive X-ray spectroscopy), X-ray diffraction or a combination thereof.
9. The ternary alloy nanoparticle catalyst according to claim 8, wherein after incorporation of different levels of the at least two transition metals, XRD shows a 2θ value of Pt fcc (111) in the range of about 39.7° to about 42°.
10. The ternary alloy nanoparticle catalyst according to any one of claims 1 to 9, wherein the ternary alloy nanoparticle catalyst is selected from PtNiCo and PtMnFe.
11. The ternary alloy nanoparticle catalyst according to claim 10, wherein the atomic ratio of the PtNiCo ternary alloy nanoparticle catalyst is about 20%-80% Pt, about 1%-50% Ni, and about 5%-40% Co.
12. The ternary alloy nanoparticle catalyst of claim 10, wherein the atomic ratio of the PtMnFe ternary alloy nanoparticle catalyst is about 15%-40% Pt, about 10%-50% Mn, and about 10%-50% Fe.
13. A method for preparing a ternary alloy nanoparticle catalyst, the ternary alloy nanoparticle catalyst comprising a platinum group metal alloyed with at least two transition metal elements, the method comprising: (a) combining the precursor of the platinum group metal and the precursor of the at least two transition metal elements with a capping agent in an organic solvent to form a slurry; (b) introducing a reducing agent into the solution to produce a colloidal suspension of the ternary alloy nanoparticle catalyst; (c) collecting and adsorbing the ternary alloy nanoparticle catalyst onto a refractory oxide support; and (d) drying and calcining the adsorbed ternary alloy nanoparticle catalyst and refractory oxide support.
14. The method according to claim 13, wherein: - the precursor of the platinum group metal is selected from platinum (II) acetylacetonate, chloroplatinic acid, platinum (II) hydroxysulfite, tetraamine platinum (II) chloride and tetraamine platinum (II) nitrate; - said precursors of said at least two transition metal elements are selected from nickel(II) acetylacetonate and cobalt(III) acetylacetonate; - the end-capping agent is selected from citric acid, polyvinyl pyrrolidone, oleylamine, oleic acid and polyethylene glycol; - the reducing agent is selected from sodium borohydride, hydrazine, formic acid, sodium formate and amine-borane complex; 1,2-hexadecanediol and oleylamine, and - The refractory oxide support is selected from the group consisting of silica, delta-alumina, theta-alumina, gamma-alumina, Si-doped alumina, alkaline earth metal stabilized alumina, transition metal stabilized alumina, zirconia and titania.
15. The method of claim 13 or 14, wherein the calcining step comprises calcining the ternary alloy nanoparticle catalyst and the refractory oxide support at about 800°C for about 2 hours in a hydrogen atmosphere, followed by heating at about 260°C for about 1 hour in air, and heating at about 590°C for about 1 hour in air.
16. The method of any one of claims 13 to 15, wherein the nanoparticles of the ternary alloy nanoparticle catalyst have an average particle size in the range of about 2 nm to about 10 nm.
17. The method of any one of claims 13 to 16, wherein the total platinum group metal content of the ternary alloy nanoparticle catalyst is from about 0.1 wt% to about 5 wt% of the metal content.
18. An exhaust treatment system comprising a ternary alloy nanoparticle catalyst according to any one of the preceding claims, the exhaust treatment system being positioned downstream of and in fluid communication with an internal combustion engine.
19. The exhaust treatment system of claim 18, wherein the exhaust treatment system is in fluid communication with the internal combustion engine via an exhaust conduit.
20. The exhaust treatment system of claim 18 or 19, wherein the exhaust treatment system further comprises a catalyzed soot filter and / or an SCR catalyst component comprising an SCR catalyst composition.
21. The exhaust treatment system of claim 20, wherein the catalyzed soot filter and / or the SCR catalyst component is located downstream of the ternary alloy nanoparticle catalyst.
22. A method for treating a gas containing hydrocarbons and / or carbon monoxide and / or NO x A method for treating an exhaust gas stream, the method comprising passing the exhaust gas stream through a ternary alloy nanoparticle catalyst or an exhaust gas treatment system according to any one of the preceding claims.
23. An oxidation catalyst composite for reducing exhaust emissions of a lean-burn engine, the oxidation catalyst composite comprising the ternary alloy nanoparticle catalyst according to any one of claims 1 to 12.
24. The oxidation catalyst composite of claim 23, wherein the oxidation catalyst composite comprises: a carrier substrate having a length, an inlet end, and an outlet end, and an oxidation catalyst catalytic material, wherein the oxidation catalyst catalytic material comprises the ternary alloy nanoparticle catalyst, The oxidation catalyst catalytic material is disposed on the carrier substrate.
25. The oxidation catalyst composite of claim 24, wherein said oxidation catalyst catalytic material comprises a washcoat, said washcoat comprising said ternary alloy nanoparticle catalyst.
26. The oxidation catalyst composite of claim 25, wherein the washcoat layer comprises a zeolite.
27. The oxidation catalyst composite of claim 25 or 26, wherein the washcoat layer comprises 5 g / ft 2 of the ternary alloy nanoparticle catalyst, calculated as an element. 3 Up to 500g / ft 3 of platinum group metals.
28. Use of the ternary alloy nanoparticle catalyst according to any one of claims 1 to 12, or the exhaust gas treatment system according to any one of claims 18 to 21, or the oxidation catalyst composite according to any one of claims 23 to 27 for treating exhaust gas of a lean-burn gasoline engine or a diesel engine.